2022
DOI: 10.3389/fphar.2022.946415
|View full text |Cite
|
Sign up to set email alerts
|

Potential drug-drug interactions in drug therapy for older adults with chronic coronary syndrome at hospital discharge: A real-world study

Abstract: Introduction: Polypharmacy are commonly observed among older adults with cardiovascular disease. However, multiple medications lead to increased risk of drug-drug interactions (DDIs). Therefore, identification and prevention actions related to harmful DDIs are expected in older adults. The study aimed to describe the prevalence of potential DDIs (pDDIs) in discharge prescriptions among older adults with chronic coronary syndrome (CCS).Methods: A single-center cross-sectional study was performed in a tertiary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 79 publications
1
7
0
Order By: Relevance
“…The prevalence of PDDIs identified by three databases was 72.1%, which was in line with the studies conducted in Spain (71.8%)20 and China (72.9%),27 but higher than other studies conducted in the oncology setting in Iran at 62.88%,39 the Netherlands at 46%2 and the USA 40. Similarly, the prevalence rate of the present study is higher in comparison with studies from other specialties such as psychiatry (68.9%),41 internal medicine (43.7%)42 and paediatrics (45.8%) 43.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…The prevalence of PDDIs identified by three databases was 72.1%, which was in line with the studies conducted in Spain (71.8%)20 and China (72.9%),27 but higher than other studies conducted in the oncology setting in Iran at 62.88%,39 the Netherlands at 46%2 and the USA 40. Similarly, the prevalence rate of the present study is higher in comparison with studies from other specialties such as psychiatry (68.9%),41 internal medicine (43.7%)42 and paediatrics (45.8%) 43.…”
Section: Discussionsupporting
confidence: 89%
“…Moderate interaction indicates that interactions have the potential to produce harm and may require treatment, and there is a need for close monitoring. Major interaction indicates that interactions produce serious clinical consequences and can cause permanent damage, and such combination should be avoided 27…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though there are defined guidelines and pharmacological therapies for the treatment of CVD, several studies have shown that polypharmacy decreases patient adherence and increases drug interactions, especially in older populations [104][105][106]. There can also be adverse side effects to these medications that have harmful consequences.…”
Section: Epigeneticsmentioning
confidence: 99%